Bagaimana Pertumbuhan Ekonomi Dan Pembangunan Infrastruktur Mempengaruhi Ketimpangan Pendapatan Di Indonesia? - Abdur-Rabb, Ahmad Faqhruddin; Andriani, Shadry; Adys, Himaya Praptani (CV. ITTC INDONESIA, 2024)
This study examines the effect of economic growth and infrastructure development on income inequality in Indonesia during the period of 2011 to 2022. To estimate the relationships between variables, the Ordinary Least Squares (OLS) technique was employed, accompanied by diagnostic tests to ensure the validity of the estimations, including residual normality, absence of multicollinearity, and absence of autocorrelation issue. The findings show that the model constructed is simultanously significant in explaining the relationship, with a relatively high degree of determination for the independent variables. Economic growth has a positive effect on income inequality, indicating that the achieved economic growth has not yet been accompanied by equitable income distribution among the population. Conversely, road infrastructure development demonstrates a significant negative effect on income inequality. This implies that improving access and connectivity through optimal road development holds substantial potential in reducing income disparities across Indonesia.